0210 Social rhythm regularity: Associations with sleep, circadian, mental health, and alcohol use outcomes in adolescents. (25th May 2022) - Tracy, Eunjin; Buysse, Daniel; Soehner, Adriane; Hasler, Brant
Abstract: Introduction: Circadian rhythms and sleep regularity relate to a range of negative health outcomes, such as mental illness and substance abuse including binge drinking. According to the social zeitgeber hypothesis, the timing of key modifiable daily behaviors serves as time cues that entrain circadian rhythms, ostensibly stabilizing them and thereby improving health. The cross-day stability in timing of these behaviors (i.e., social rhythm regularity) is measured by SRM5; however, studies have not tested whether SRM5 correlates with circadian rhythm regularity based on physiological measures, such as dim light melatonin onset (DLMO). The current study examined whether SRM5 was associated with: (1) the regularity of circadian rhythms and/or sleep regularity metrics, and (2) sleep quality, depression, and binge drinking. Methods: Late adolescents aged 18 to 22 years old who drink alcohol (n = 36; 61.1% female, Mage = 21.26) completed a self-reported sleep diary (including SRM5 items for first contact, start work, and dinner time), wore a wrist actigraph for 14 days, and completed 2 overnight visits to assess DLMO. We used the self-reported data to calculate SRM5 and standard deviation (StDev); actigraphy data to calculate composite phase deviation (CPD), social jet lag (SJL), and interdaily stability (IS); and DLMO data to calculate the stability of the circadian phase (Sunday minus Thursday). Participants also completed surveys that assessed global sleep quality, depressive symptoms, and frequency of binge drinking. Correlational analysis and hierarchical linear regression modeling were used. Results: Higher SRM5 scores (i.e., higher social rhythm regularity) were associated with higher regularities of mid-sleep timing (r = –.48, p < .001) and total sleep duration (r = –.41, p = .01) based on StDev metrics but were not associated with IS (r = 13, p = .45), CPD (r = –.19, p = .28), SJL (r = –.07, p = .68), and stability of DLMO (r = –.003, p = .99). A post-hoc analysis found that higher stability of the "out of bed" item of SRM5 was related to higher stability of DLMO (b = –.11, se = .05, p = .03, r2 = .33). Higher SRM5 scores were associated with better sleep quality (b = –.73, se = .30, p = .02, r2 = .21), but were not with depressive symptoms or binge drinking Conclusion: In contrast with the social zeitgeber hypothesis, SRM5 was not associated with circadian rhythm regularity measured by DLMO. However, social rhythm regularity is an important factor in predicting better sleep quality. This study provides a foundation for future research with better power to determine the extent to which social rhythms influence circadian stability and to better understand why social rhythm regularity relates to sleep quality. Support (If Any): This research was supported by the NIH NIAAA (R21AA023209-02 ), NHLBI (T32HL082610), and NIMH (T32MH019986)